2020
DOI: 10.1111/febs.15324
|View full text |Cite
|
Sign up to set email alerts
|

Reverse protein engineering of a novel 4‐domain copper nitrite reductase reveals functional regulation by protein–protein interaction

Abstract: Cu‐containing nitrite reductases that convert NO2‐ to NO are critical enzymes in nitrogen‐based energy metabolism. Among organisms in the order Rhizobiales, we have identified two copies of nirK, one encoding a new class of 4‐domain CuNiR that has both cytochrome and cupredoxin domains fused at the N terminus and the other, a classical 2‐domain CuNiR (Br2DNiR). We report the first enzymatic studies of a novel 4‐domain CuNiR from Bradyrhizobium sp. ORS 375 (BrNiR), its genetically engineered 3‐ and 2‐domain var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
3
10
0
Order By: Relevance
“…Hydrophobic residues substituting Asn107 were also observed in the two‐domain rhizobial NirKs from Bradyrhizobium sp. ORS 375 ( Br 2D NirK) and B. japonicum USDA110 ( Bj NirK), both showing turnover numbers lower than those of Af NirK and Ac NirK 17,37 . In line with this observation, Sm NirK has a hydrophobic Val residue at this position and, as reported in our previous work, MV‐dependent activity of Sm NirK shows only 12% of the Ax NirK maximum turnover 22 .…”
Section: Resultssupporting
confidence: 86%
“…Hydrophobic residues substituting Asn107 were also observed in the two‐domain rhizobial NirKs from Bradyrhizobium sp. ORS 375 ( Br 2D NirK) and B. japonicum USDA110 ( Bj NirK), both showing turnover numbers lower than those of Af NirK and Ac NirK 17,37 . In line with this observation, Sm NirK has a hydrophobic Val residue at this position and, as reported in our previous work, MV‐dependent activity of Sm NirK shows only 12% of the Ax NirK maximum turnover 22 .…”
Section: Resultssupporting
confidence: 86%
“…We have recently identified a blue CuNiR from Bradyrhizobium ORS 375 of the order Rhizobiales (Br 2D NiR) (21). The catalytic efficiency of Br 2D NiR was found to be substantially lower than two of the well-studied two-domain CuNiRs representing the blue (AxNiR) and green (AcNiR) subclasses, despite a sequence identity of ~70% (21). The blue crystals of Br 2D NiR proved amenable to soaking of substrate and yielded highly diffracting crystals, providing a unique opportunity to obtain atomic-resolution structures of up to 1 Å with synchrotron x-rays and damage-free FRIC structures using XFEL, to ~1.3 Å resolution of as-isolated, nitrite-and nitric oxide-bound states.…”
Section: Introductionmentioning
confidence: 99%
“…It has been identified in species from Rhizobiales order, such as Bradyrhizobium sp. ORS 375 [62]. They contain the core domain of "classical" two-domains NirK (cupredoxin domain) to which both a cytochrome c and cupredoxin domain are tethered at the N terminus [62].…”
Section: Respiratory Nitrite Reductasementioning
confidence: 99%
“…ORS 375 [62]. They contain the core domain of "classical" two-domains NirK (cupredoxin domain) to which both a cytochrome c and cupredoxin domain are tethered at the N terminus [62]. Recent studies reported a division of NirK sequences into two different phylogenetic clades.…”
Section: Respiratory Nitrite Reductasementioning
confidence: 99%
See 1 more Smart Citation